Molecular Characterization of Staphylococci Recovered from Hospital Personnel and Frequently Touched Surfaces in Tianjin, China - Yuting Liu; Liqin Chen; Yuping Duan; Zhen Xu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Staphylococci are major hospital-associated pathogens, and the dissemination of methicillin-resistant staphylococci in hospitals poses a great challenge for managing hospital-acquired infections. Little is known about the dissemination of staphylococci recovered from the hospital environment and personnel in China. In this study, antimicrobial susceptibility tests, mecA gene detection, SCCmec typing, and multilocus sequence typing (MLST) were performed to clarify the molecular epidemiology of staphylococci in a large hospital in Tianjin, China. One hundred and ninety-five staphylococci were recovered, and 94% of isolates were resistant to at least one antibiotic. Eighty-five staphylococci were mecA gene-positive, and 40% of them harbored SCCmec IV and V. The genotype of Staphylococcus aureus (S. aureus) was ST25, and the dominant genotype of methicillin-resistant Staphylococcus epidermidis (MRSE) was ST59. Three new sequence types were assigned as ST840, ST841, and ST842. One (2%) frequently touched surface was contaminated by S. aureus, which suggested that environmental contamination occurred in the hospital in China. Nineteen (39%) frequently touched surfaces were contaminated by methicillin-resistant coagulase-negative staphylococci (MRCoNS), and 46% of HP carried MRCoNS. Varied staphylococcal species and antimicrobial-resistance rates were observed between staphylococci that were recovered from hospital personnel and frequently touched surfaces. The transmission of MRSE and S. aureus between hospital personnel and frequently touched surfaces was detected. Hospital items and personnel may act as reservoirs of antimicrobial-resistant staphylococci, and cleaning strategies should be carried out to decrease the dissemination of antimicrobial-resistant staphylococci in hospitals in China.